The protective role of Lactobacillus rhamnosus GG postbiotic on the alteration of autophagy and inflammation pathways induced by gliadin in intestinal models - Furone, Francesca; Bellomo, Claudia; Carpinelli, Martina; Nicoletti, Martina; Hewa-Munasinghege, Francesca Natasha; Mordaa, Majed; Mandile, Roberta; Barone, Maria Vittoria; Nanayakkara, Merlin (Frontiers in Medicine, 2023)
Celiac disease (CD) is an autoimmune enteropathy caused by an abnormal immune response to gliadin peptides in genetically predisposed individuals. The only therapy available today is a gluten free diet (GFD) to keep for life. Innovative therapies include probiotics and postbiotics as nutritional supplements, both can benefit the host. Therefore, the aim of the study was to investigate possible beneficial effects of the Lactobacillus Rhamnosus GG (LGG) postbiotic in preventing the effects induced by indigested gliadin peptides on the intestinal epithelium. We evaluated these effects on the mTOR pathway, autophagic function and inflammation. We stimulated the Caco-2 cells with the undigested gliadin peptide (P31-43), and crude gliadin peptic-tryptic peptides (PTG) and pretreated the samples with the LGG postbiotic (ATCC 53103) (1x108). We investigated the effects induced by gliadin before and after pretreatment. Levels of phosphorylation of mTOR, p70S6K/ p4EBP-1 were increased after treatment of PTG and P31-43 indicating that intestinal epithelial cells responded to the gliadin peptides activating the mTOR pathway. Moreover, we observed an increase of phosphorylation of NF-κβ. Pretreatment with LGG postbiotic prevented both the mTOR pathway activation and the NF-κβ phosphorylation. P31-43 reduced LC3II staining and postbiotic treatment was able to also prevent this reduction. After that, to evaluate the inflammation in a more complex intestinal model, we have cultured intestinal organoids derived from celiac patient biopsies (GCD-CD) and controls (CTR). The stimulation with peptide 31-43 in intestinal CD organoids induced NF-κβ activation and pretreatment with postbiotic LGG could prevent it. These data show that LGG postbiotic can prevent the P31-43 mediated increase of inflammation both in Caco-2 cells and in intestinal organoids from CD patients.